Cracking of used vegetable oil mixed with polypropylene waste in the presence of activated carbon - Sommani, Piyanart (ASEAN engineering journal)
With respect to high energy demand and increasing price of fossil fuels, alternative energy is a concerned issue worldwide. Waste cooking oils and plastic wastes are attractive as starting materials for value creation due to their high existing volumes and cost saving from waste treatment. Therefore, in this work, liquid fuel was synthesized by cracking of used vegetable oil (UVO) mixed with polypropylene waste (PP) in the presence of activated carbon from coconut shell. The reactions were studied at a constant hydrogen pressure of 0.1 MPa in a batch reactor. The weight ratios of used vegetable oil and polypropylene waste were varied at 30 : 70, 50 : 50 and 70 : 30 with activated carbon to raw materials ratios of 2.5 and 5 wt% at the reaction temperature of 390 and 430°C, and reaction time of 30 and 60 mins. The amounts of gas, liquid and solid fractions were analyzed. The highest yield of total liquid hydrocarbon product was attained at a ratio of used vegetable oil to polypropylene waste of 30 : 70 wt% with activated carbon to raw materials ratios of 2.5 wt%, reaction temperature of 430°C and reaction time of 30 mins. Under these conditions, gas, liquid and solid fractions of 19.56, 79.69 and 0.75 wt% were observed. The distribution of oil fractions in liquid product was analyzed by the simulated distillation gas chromatography based on ASTM D2887, which is the standard test method for the boiling-range distribution of petroleum fractions. It was comprised of naphtha, kerosene, light gas oils, heavy gas oils and long residue of 33.20, 14.62, 19.72, 2.49 and 9.66 wt%, respectively.